Highly stable silver (I) coordination complex as efficient photocatalyst for the degradation of organic dyes in water. (2nd May 2020) - Xu, Chanchan; Lu, Lu; Lv, Le; Guo, Jiandong; Luo, Chaoyun; Luo, Dawei; Liu, Wei
Abstract: A new zero-dimensional (0D) silver (I) chloride based coordination complex 0 D-Ag2 Cl2 (L) (1, L = (oxybis(2, 1-phenylene))bis(diphenylphosphine)) has been prepared by mixing the silver(I) salt and a bidentate P-ligand at room temperature in solution. 1 exhibits a band gap of 3.5 eV and a decomposition temperature (Td ) of 280 °C. Such a high Td for molecular complex is a result of the strong Ag-P bonding and the "chelating effect" of the metal of the bidentate P-ligand. It has been used as an efficient photocatalyst for the degradation of organic dyes in water.